A Hydrogel-Based Self-Sensing Underwater Actuator - Shuyu Wang; Zhaojia Sun; Shuaiyang Duan; Yuliang Zhao; Xiaopeng Sha; Shifeng Yu; Lei Zuo (Micromachines, 2022)
Soft robots made of hydrogels are suited for underwater exploration due to their biocompatibility and compliancy. Yet, reaching high dexterity and actuation force for hydrogel-based actuators is challenging. Meanwhile, real-time proprioception is critical for feedback control. Moreover, sensor integration to mimic living organisms remains problematic. To address these challenges, we introduce a hydrogel actuator driven by hydraulic force with a fast response (time constant 0.83 s). The highly stretchable and conductive hydrogel (1400% strain) is molded into the PneuNet shape, and two of them are further assembled symmetrically to actuate bi-directionally. Then, we demonstrate its bionic application for underwater swimming, showing 2 cm/s (0.19 BL/s) speed. Inspired by biological neuromuscular systems’ sensory motion, which unifies the sensing and actuation in a single unit, we explore the hydrogel actuator’s self-sensing capacity utilizing strain-induced resistance change. The results show that the soft actuator’s proprioception can monitor the undulation in real-time with a sensitivity of 0.2%/degree. Furthermore, we take a finite-element method and first-order differential equations to model the actuator’s bending in response to pressure. We show that such a model can precisely predict the robot’s bending response over a range of pressures. With the self-sensing actuator and the proposed model, we expect the new approach can lead to future soft robots for underwater exploration with feedback control, and the underlying mechanism of the undulation control might offer significant insights for biomimetic research.